HUBUNGAN KUALITAS TIDUR DENGAN TEKANAN DARAH PADA PERAWAT DI SILOAM HOSPITALS MANADO - Subagiartha, Farel Stepanus; Katuuk, Mario Esau; Paat, Toar Calvin Christo (JURNAL KEPERAWATAN, 2024)
Background: Sleep quality is one of the factors that can affect blood pressure. Factors that affect the quality of sleep is work with a shift system, one of which works as a nurse. The Aim was to analyze the relationship between sleep quality and blood pressure in nurses. The Methods is used an analytic observational research design, with a cross-sectional approach that was tested using the Spearman Rank correlation test. The Sample was determined using a non-probability sampling technique, using a purposive sampling method, and to determine the sample size of this study using the Slovin formula, and obtained a total sample of 72 respondents. The Results is obtained p value = 0.042 (p = <0.05) and r value = 0.241. The Conclusion is that there is a relationship between sleep quality and blood pressure in nurses with a low level of correlation strength and has a positive correlation direction or the correlation coefficient value of the two variables has a relationship direction that is directly proportional. The Suggestion is that it is hoped that screening can be carried out for further preventive and curative actions. Keywords: Blood pressure; Nurse; Sleep quality